A changing climate is snuffing out post‐fire recovery in montane forests. Issue 11 (17th August 2020) - Rodman, Kyle C.; Veblen, Thomas T.; Battaglia, Mike A.; Chambers, Marin E.; Fornwalt, Paula J.; Holden, Zachary A.; Kolb, Thomas E.; Ouzts, Jessica R.; Rother, Monica T.
Abstract: Aim: Climate warming is increasing fire activity in many of Earth's forested ecosystems. Because fire is a catalyst for change, investigation of post‐fire vegetation response is critical to understanding the potential for future conversions from forest to non‐forest vegetation types. We characterized the influences of climate and terrain on post‐fire tree regeneration and assessed how these biophysical factors might shape future vulnerability to wildfire‐driven forest conversion. Location: Montane forests, Rocky Mountains, USA. Time period: 1981–2099. Taxa studied: Pinus ponderosa ; Pseudotsuga menziesii . Methods: We developed a database of dendrochronological samples ( n  = 717) and plots ( n  = 1, 301) in post‐fire environments spanning a range of topoclimatic settings. We then used statistical models to predict annual post‐fire seedling establishment suitability and total post‐fire seedling abundance from a suite of biophysical correlates. Finally, we reconstructed recent trends in post‐fire recovery and projected future dynamics using three general circulation models (GCMs) under moderate and extreme CO2 emission scenarios. Results: Though growing season (April–September) precipitation during the recent period (1981–2015) was positively associated with suitability for post‐fire tree seedling establishment, future (2021–2099) trends in precipitation were widely variable among GCMs, leading to mixed projections of future establishment suitability. In contrast, climatic water deficit (CWD), which is indicative of warm, dry conditions, was negatively associated with post‐fire seedling abundance during the recent period and was projected to increase throughout the southern Rocky Mountains in the future. Our findings suggest that future increases in CWD and an increased frequency of extreme drought years will substantially reduce post‐fire seedling densities. Main conclusions: This study highlights the key roles of warming and drying in declining forest resilience to wildfire. Moisture stress, driven by macroclimate and topographic setting, will interact with wildfire activity to shape future vegetation patterns throughout the southern Rocky Mountains, USA.